2016
DOI: 10.1149/2.0171606jes
|View full text |Cite
|
Sign up to set email alerts
|

Considerations on the Chemical Toxicity of Contemporary Li-Ion Battery Electrolytes and Their Components

Abstract: The objective of this study is to evaluate chemical hazards and risks associated with the accidental release of Li-ion battery electrolyte into an enclosed space. Because of the high volatility and reactivity of some components of contemporary Li-ion battery electrolytes this study focuses on the inhalation toxicity of released and generated gas phase components. These include evaporated solvents and HF as a decomposition product of the widely used LiPF 6 salt. Our calculations show that at room temperature a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
77
0
6

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 115 publications
(84 citation statements)
references
References 36 publications
(60 reference statements)
1
77
0
6
Order By: Relevance
“…Acetonitrile (ACN), for instance, has ah igh dielectric constant (e = 35.9) [12] and high solvating power but alower viscosity than carbonates.These properties are attractive for high-power applications,w hich are very demanding in terms of ionic transport, despite the higher vapor pressure of ACNc ompared to carbonates. [13] ACN electrolytes are currently applied in supercapacitors. [14] However,A CN is thermodynamically unstable in the presence of Li metal and, in contrast to cyclic carbonates,cannot form an in situ SEI.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Acetonitrile (ACN), for instance, has ah igh dielectric constant (e = 35.9) [12] and high solvating power but alower viscosity than carbonates.These properties are attractive for high-power applications,w hich are very demanding in terms of ionic transport, despite the higher vapor pressure of ACNc ompared to carbonates. [13] ACN electrolytes are currently applied in supercapacitors. [14] However,A CN is thermodynamically unstable in the presence of Li metal and, in contrast to cyclic carbonates,cannot form an in situ SEI.…”
mentioning
confidence: 99%
“…[15] Furthermore,the role of ACN solvent in HF formation during the decomposition of LiPF 6 remains to be demonstrated. [13] Am ajor step towards the application of ACNi nL ib atteries was accomplished by Yamada et al,when they demonstrated the stability of ACN under reductive conditions and the electrochemically reversible lithiation of graphite in superconcentrated ACNelectrolyte (4.2 m Li bis(trifluoromethanesulfonyl)imide (LiTFSI)). [16] They proposed that the chemical stability comes from the lack of free solvent molecules in the electrolyte,i nhibiting ACNi nsertion into the graphitic layers.…”
mentioning
confidence: 99%
“…Such ap assivation layer can be formed in situ, as the electrochemical potential of the Li metal is sufficiently low to initiate the electrolyte reduction that leads to formation of the solid electrolyte interphase (SEI). [13] ACN electrolytes are currently applied in supercapacitors. [7] TheSEI layer permits Li + ion transport from the bulk to the Li metal electrode and hinders the continuous consumption of the electrolyte,that is,infinite Li + consumption.…”
mentioning
confidence: 99%
“…An effective SEI layer requires ah omogeneous chemical composition and morphology and ahigh ionic conductivity. [13] Am ajor step towards the application of ACNi nL ib atteries was accomplished by Yamada et al,when they demonstrated the stability of ACN under reductive conditions and the electrochemically reversible lithiation of graphite in superconcentrated ACNelectrolyte (4.2 m Li bis(trifluoromethanesulfonyl)imide (LiTFSI)). Intensive efforts have been made to mimic this passivation layer via achemical treatment to modify its surface and deliberately create aphysical barrier (artificial SEI).…”
mentioning
confidence: 99%
See 1 more Smart Citation